(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the continuing legacy of George Orwell’s Nineteen Eighty-Four (1949) within British dystopian fiction from 1984 to the present day. Drawing on Claire Wrobel’s article The Legacy of Nineteen Eighty-Four: British Dystopias, from 1984 to the Present Day (2022), it explores how Orwell’s themes of surveillance, language, truth, and political manipulation have evolved in response to shifting socio-political contexts — from the Cold War and neoliberalism to the digital and ecological crises of the twenty-first century. The analysis focuses on key British dystopian works, including Margaret Atwood’s The Handmaid’s Tale (although Canadian, deeply tied to British tradition), Kazuo Ishiguro’s Never Let Me Go (2005), Julian Barnes’ England, England (1998), and J.G. Ballard’s late fiction. The study argues that contemporary British dystopia has transformed Orwell’s totalitarian paradigm into a pluralistic critique of post-industrial, technocratic, and ecological anxieties while retaining the ethical urgency of Orwell’s vision.